FAKTOR YANG MEMENGARUHI KEAKTIFAN IBU BALITA KE POSYANDU DI DESA PENGGALANGAN KECAMATAN SEI BAMBAN KABUPATEN SERDANG BEDAGAI - Qori Armiza Septia; Siti Halimah; Tharra Widadari Aldinda (Ensiklopedia of Journal, 2023)
The high infant and toddler mortality rate in Indonesia is one indicator of the degree of public health that is considered to still need attention from the government. Posyandu is a form of Community Resource Health Effort managed with the community, its function is to strive to reduce the mortality rate of toddlers. The purpose of this study is to analyze the influence of age, education, occupation, and knowledge of mothers on the activity of mothers under five to Posyandu in Penggalangan Village, Sei Bamban District, Serdang Bedagai Regency in 2021. This research design uses an analytical survey with a cross sectional approach. The population was 72 people with sampling using a total sampling technique of 72 people. Data collection techniques use primary, secondary and tertiary data with questionnaire measuring instruments. Data analysis was performed univariately, bivariately using chi-square and multivariate using logistic regression tests. The results of this study showed the influence of age, education, work and knowledge factors on the activeness of mothers under five to posyandu with (p value = 0.0040.05), (p value = 0.0050.05), (p value = 0.0010.05), (p value = 0.0080.05). The logistic regression test, the most dominant factor influencing the activity of mothers of toddlers to posyandu is work with an Exp (B) value of 5,464.  In conclusion, there are influences of age, education, work, and knowledge that affect the activity of mothers of toddlers to posyandu in the raising village of Sei Bamban District, Serdang Bedagai Regency in 2021. It is recommended that health workers should further increase the knowledge of mothers of toddlers through counseling about the importance of active mothers of toddlers to posyandu.